Networks of solidarity and intersections in literature and gender - Souza, Davi Silistino de [UNESP]; Ceneviva Nigro, Claudia Maria [UNESP]; Morais, Fernando Luis de [UNESP]; Rodrigues Benfatti, Flavia Andrea; Passos, Leandro [UNESP]; Soares, Luiz Henrique [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2020)
This article aims to analyze the importance of the different forms of networks of solidarity and intersectionality for the national feminist approach and for contemporary gender studies. We understand that the criticisms from these studies seek to question the role of characters considered subaltern by the Western patriarchal tradition, achieving voice and space in the production of subaltern writers. Our critical emphasis, however, rests mainly on gender studies, as they present more openness to union and the establishment of mutual aid with other minorities (LGBTQI+, women and men of different ethnicities, among others). Thus, in this work, the conception of networks of solidarity within gender studies is discussed, in order to review the colonial heterarchies, through which racist, sexist, homophobic, segregationist ideologies, among others, are perpetuated. The efforts of contemporary researchers and writers presenting networks of solidarity and the concept of intersectionality contribute to the expansion of knowledge and respect for others, demonstrated through moments of confrontation and manifestations of subalterns.
Keywords: Contemporaneity; Gender Studies; Intersectionality; Judith Butler; Kimberle Crenshaw; Literature; Network of Solidarity